A novel Frizzled 7 antibody disrupts the Wnt pathway and inhibits Wilms tumor growth - Vax, Einav; Caspi, Revital; Shukrun, Rachel; Pode-Shakked, Naomi; Pleniceanu, Oren; Golan, Hana; Namestnikov, Michael; Mark-Danieli, Michal; Markovsky, Ela; Bar-Lev, Dekel D.; Barshack, Iris; Satchi-Fainaro, Ronit; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Frizzled 7 (FZD7), a Wnt receptor that activates canonical Wnt/β-catenin signaling, has been implicated in multiple cancers, including Wilms tumor (WT), the most common pediatric kidney malignancy. We previously identified FZD7 as a marker of the WT cancer stem cell population and a potential therapeutic target. To evaluate this, we generated a panel of monoclonal anti-FZD7 antibodies using epitope mapping of the receptor and assessed their functional activity in primary WT cells and xenograft models. Among the panel, clone 288.1 induced significant cell death in primary Wilms tumor cells and inhibited cell proliferation and migration. This effect correlated with canonical Wnt signaling inhibition, a reduction in activated β-catenin and downregulation of Wnt/β-catenin target genes concomitant with diminished Wilms tumor cancer stem cell (CSC) markers. In vivo, treatment with anti-FZD7-288.1 significantly inhibited WT xenograft growth, resulting in reduced tumor volume. These findings demonstrate that FZD7 is a critical driver of Wilms tumor progression and support antibody-mediated FZD7 blockade as a promising therapeutic strategy.